An Overview of the Creative Drama Experience in The Information Technologies And Software Course From The Students' Perspective - Gökhan KARAOSMANOĞLU; Ömer ADIGÜZEL (Anı Publishing, 2021)
This study aimed to determine the opinions of 6th-grade Information Technologies and Software Course (ITSC) students on the creative drama method. In the first stage of the study, which was designed with the basic qualitative research method, a drama study prepared for the 6th-grade ITSC was applied to a group of 35 students. Focus group interviews were conducted with 24 students at the end of the drama study. Content analysis was used in the analysis of the qualitative data obtained in the study. Research findings showed that creative drama is effective in realizing the achievements of ITSC, in better for expressing students for themselves, in using information technologies, the internet, and social media in their real-life consciously. The results of the research revealed that the drama method and techniques used are effective for students to better understand the subjects covered, focus on the lesson, participate in the lesson more eagerly, feel better during the lesson, and the method in question positively affects their emotions. In this process, the students stated that the games, role-playing and improvisation exercises, and physical activities adapted according to the learning outcomes of the lesson made them more interested and enthusiastic about the lesson. According to the results of the research, it can be suggested that the use of drama methods and techniques in different ways in ITSC should be widespread and the teachers of the ITSC should be educated about drama and should use drama method and techniques in student's learning processes.